Kekuatan Hukum Surat Keterangan Ahli Waris bagi Golongan Bumiputera yang Dikuatkan oleh Camat - Monika Ardia Ningsi Massora; Victoria Pasari Putri (Notaire, 2019)
Legal Heir Certificate is as a letter issued by an authorized official or government agency or the heirs itself. With the presence of different officials/agencies who have the authority in publishing and making a legal heir certificate, there are various systems of Indonesian hereditary law that give rise to legal pluralism. One of the agencies known as the Head of Sub-district has the authority to issue legal heir certificate for Indonesian citizens in Bumiputera group. It contains all the names of the heirs who are entitled to receive the inheritance as well as the divided portion or part of each inheritance. In this matter, the Village Head (Lurah) and the Sub-district Head (Camat) are state administrative officials whose duty is to carry out government affairs by issuing state administrative decisions. Legal heir certificate as an instrument that can prove whether someone is truly an heir or not is evidence in the field of civil law. Keywords: Bumiputera Group; Sub-district Head Authority; Legal Heir Certificate